Associations of Alcohol Dehydrogenase and Aldehyde Dehydrogenase Polymorphism With Cognitive Impairment Among the Oldest-Old in China - Jin, Xurui; Long, Tingxi; Chen, Huashuai; Zeng, Yi; Zhang, Xian; Yan, Lijing; Wu, Chenkai (Frontiers in Aging Neuroscience, 2022)
Recent literature suggested that ALDH2 mutation is associated with alcohol metabolism, and ethanol intake might jointly increase the risk of Alzheimer’s disease (AD) in mice. However, it is unclear whether this synergistic effect exists among humans. We examined the associations of four single nucleotide polymorphisms (SNPs) on aldehyde dehydrogenase (ALDH) and alcohol dehydrogenase (ADH) genes (i.e., ALDH2 rs671, ADH1B rs1229984, ADH1B rs1042026, and ADH1C rs1693482) and cognitive impairment among the oldest-old. We also investigated whether this association was modified by ethanol intake from alcohol consumption. Data were from the Chinese Longitudinal Healthy Longevity Survey genetic sub-study, including 1,949 participants aged over 90 years. Participants with a Mini-Mental State Examination (MMSE) score of < 18 were considered cognitively impaired. Alcohol consumption was categorized as heavy, moderate, or never drinkers. With the dominant model, carrying A allele on rs671, C allele on rs1229984, and T allele on rs1042026 was associated with 33% (95% confidence interval [CI]: 5%, 69%), 33% (95% CI: 2%, 75%), and 29% (95% CI: 3%, 62%) higher odds of cognitive impairment in the multivariable-adjusted logistic model, respectively. We did not observe a significant interaction between those SNPs and alcohol consumption. Among the oldest-old, carrying ALDH2 rs671 mutation was associated with higher odds of cognitive impairment independent of alcohol consumption.